No association between processing speed and risk of sport-related concussion in youth soccer - Lopez-Flores, R.; Oldham, J.; Howell, D.; Rush, J.; Taylor, A.; Berkner, P.; Mannix, R.; Meehan, W. P. III (Clinical Journal of Sport Medicine, 2022)
Objective: To determine whether slow processing speed is associated with risk of sport-related concussion. Design: We conducted a retrospective cohort study using computerized neurocognitive assessments (Immediate Post-concussion Assessment and Cognitive Testing [ImPACT]) from the Massachusetts Concussion Management Coalition. Slow processing speed was defined as 2 SD below the sample mean (n = 131) and fast processing speed as 2 SD above the sample mean (n = 259). We used a binary logistic regression model to determine the odds of sustaining a concussion with our main predictor being processing speed (high or low) adjusted for the effects of age, sex, and prior number of concussions. Setting: Massachusetts Concussion Management Coalition, Institutional care. Participants: Three hundred ninety junior high soccer players ages 10 to 15 with a baseline score for ImPACT. Independent Variables: Processing Speed. Main Outcome Measures: Risk of sustaining a concussion. Results: Those with slow processing speed had a visual motor composite score of =19.92, those with fast-processing speed had a score of =46.20. Athletes with slow processing speed were younger (13 vs 14 years; P < 0.001) and more likely to be male (57% vs 49%; P = 0.014). After adjusting for the effects of age, sex, and prior concussions, there was no significant difference in the odds of sustaining a concussion between groups (aOR 1.01; 95% CI, 0.99-1.04). Conclusions: Despite previous research showing that slow processing speed is a risk factor for musculoskeletal injuries during sports, our study suggests that processing speed is not associated with the risk of sustaining a concussion among junior high school soccer players.